Social safeness and self-compassion in the relationship between shame and depression in sexual minorities: A moderated-mediation model - Ribeiro, Andreia Alexandra Gil Manão Alves (2022)
Dissertação de Mestrado em Intervenções Cognitivo-Comportamentais em Psicologia Clínica e da Saúde apresentada à Faculdade de Psicologia e de Ciências da Educação